REPRESENTASI MAKNA KEPERCAYAAN DIRI FILM WORDS BUBBLE UP LIKE SODA POP - Lestari, Suci; Fadhillah, Sarrah Kurnia (Jurnal Sarjana Ilmu Komunikasi (J-SIKOM), 2024)
This research discusses the representation of belief in the film Words Bubble Up Like Soda Pop produced by Sublimation and Signal.MD. The aim of this research is to describe the attitude of self-confidence depicted in the animated film Words Bubble Up Like Soda Pop. To describe this problem, the researcher used a descriptive method with a qualitative approach and with Roland Barthes' Semiotic Analysis knife to look at the connotative, denotative and myths conveyed in it. After carrying out these processes, the researcher will draw conclusions so that they find the representation in the words bubble up like soda pop. The results of this research show that there are several representations of self-confidence depicted in this film. Among them are the representation of (1) believing in one's own abilities, (2) acting independently in making decisions, (3) having a positive feeling towards oneself, (4) daring to express one's opinion. Through this research, it is hoped that messages of self-confidence contained in the animated film Words Bubble Up Like Soda Pop can be implemented in everyday life, not only that, it is also hoped that workers and film business owners will contribute to the production of domestic animated films that are suitable for broadcast and have many moral messages for young people or for the audience as well as under parental supervision for watching films for children Keywords :Roland Barthes Semiotic Analysis, Representation, Self-Confidence, Words Bubble Up Like Soda Pop